HUMAN EXCRETA DISCHARGING SYSTEM AND POTENTIAL NUTRIENT RECOVERY OF ECOLOGICAL SANITATION CONCEPT IS IMPLEMENTED IN SLUM AREA OF KIARACONDONG, BANDUNG - Astuti, Jovita Tri; Nilawati, Dewi; Sintawardani, Neni; Ushijima, Ken (Teknologi Indonesia, 2016)
This study was aimed to observe sanitation conditions of Kiaracondong and to estimate potential recovery of nutrient from human excreta. Interviews to 111 households covering of defecation frequency, toilet facilities, water sources and discharge systems were conducted through cooperation with the household association. Fresh faeces and urine samples were collected, weighed and characterized. Data of Kiaracondong population was required to calculate the nutrient recovery potential based on human excreta characteristics. The results showed that all public toilets in Kiaracondong, which were installed along the canals, have no water facilities and are in poor sanitation conditions. Wastewater from all public toilets and most private toilets were discharged directly to water bodies. Potential nutrients recovery from human excreta were 57.32, 2.79, 1.57, and 1.65kg.p -1 .y -1 , for OM, N, P, and K respectively. Meanwhile, total nutrient recovery in Kiaracondong was estimated to be 7,199; 350’ 197; and 207 tons.y -1 for OM, N, P, and K respectively. Worm ova was not detected in faeces and urine samples. However, bacteria E. coli and Enterobacter agglomerans and fungus Candida sp. were detected in faeces samples. Meanwhile, organisms in urine were E. coli, Enterobacter aglomerans, Serratia liquefaciens, Serratia marcescens and Staphylococcus saprophyticus. Implementation of composting toilet was expected could be appropriately way to solve the sanitation problems.